Hydrazine-assisted formation of ultrathin MoS2 nanosheets for enhancing their co-catalytic activity in photocatalytic hydrogen evolution. Issue 15 (28th March 2017) - Reddy, D. Amaranatha; Park, Hanbit; Hong, Sangyeob; Kumar, D. Praveen; Kim, Tae Kyu
Abstract : This work demonstrates a simple and effective approach using hydrazine to modulate the active sites and electrical conductivity of MoS2 with the aid of ultrasonication. Abstract : We demonstrate a simple and effective approach to modulate the active sites and electronic properties of MoS2 using hydrazine assisted liquid exfoliation for enhancing its co-catalytic activity in photocatalytic hydrogen evolution. The resulting ultrathin MoS2 (HUT-MoS2 ) nanosheets integrated on CdS nanorods, from hydrazine assisted liquid exfoliation, exhibit an excellent hydrogen evolution rate of 238 mmol g −1 h −1 under natural sunlight, which is the best performance ever reported for CdS/MoS2 -based nanostructures. The apparent quantum yield reached 53.3% at 425 nm in 5 h. The hydrogen evolution rate was influenced by several experimental parameters, such as the photocatalyst dose, sacrificial donor concentration, and amount of co-catalyst on CdS, which were investigated in detail. More importantly, the CdS/HUT-MoS2 nanocomposite showed remarkable photo-stability for up to 100 h. The excellent hydrogen evolution performance and stability may be due to the unique structure and properties of HUT-MoS2 nanosheets, which significantly boosted the charge transportation between CdS and HUT-MoS2 and suppressed charge recombination, thus favoring the involvement of more electrons in hydrogen production. We believe that the presented nanohybrid design strategy and the implementation of this noble metal-free co-catalyst enable the development of inexpensive robust co-catalysts for sustainable hydrogen production to satisfy the growing global energy demand and address environmental problems.